Reversal agents for direct oral anticoagulants: considerations for hospital physicians and intensivists. Issue 3 (27th May 2019) - Desai, Nihar R.; Cornutt, David
ABSTRACT: Direct oral anticoagulants (DOACs) include dabigatran etexilate, a direct thrombin inhibitor, and specific inhibitors of activated coagulation factor X (FXa; e.g. apixaban, betrixaban, edoxaban, rivaroxaban). DOACs are associated with lower rates of major and fatal bleeding events compared with warfarin. Clinicians may need to achieve rapid reversal of anticoagulation effects of the DOACs in an emergency setting. Idarucizumab and andexanet alfa, which reverse the anticoagulant effects of dabigatran and FXa inhibitors, respectively, are DOAC reversal agents available in the US. Other reversal agents (e.g. ciraparantag for heparins, DOACs) are in development. Alternative nonspecific agents (e.g. fresh frozen plasma, prothrombin complex concentrate) are available. Nonspecific prohemostatic agents can counteract the anticoagulant action of DOACs in emergency situations, when specific reversal agents are unavailable. However, specific reversal agents are efficacious and safe and should be preferred when available. In this review, we discuss practical issues in the initiation of DOAC therapy, situations where reversal may be needed, coagulation assays, reversal agents, and post-reversal complications in the context of published evidence and guidelines.